ANALYSIS OF EARTHQUAKE SEISMICITY IN MALUKU PROVINCE AND ITS SURROUNDING AREAS USING THE MAXIMUM LIKELIHOOD ESTIMATION METHOD - Wattimanela, Henry Junus; Setiawan, Adi (PATTIMURA UNIVERSITY, 2025)
Tectonic earthquakes are natural disasters that occur abruptly over a relatively short period, resulting from the movement of tectonic plates. The Maluku region is classified as prone to seismic activity due to its geographical location at the confluence of three tectonic plates: the Eurasian, Pacific, and Indo-Australian. This study aims to analyze the seismic activity of earthquakes in the Maluku region and its surrounding areas. The methodology employed is based on Descriptive Statistics and Maximum Likelihood Estimation. The data set was obtained from the International Seismological Centre (ISC) and comprises earthquakes occurring in the Maluku region and surrounding areas between 1970-2023. The earthquakes were selected based on the criteria of magnitude > 3.8 Mw and depth < 60 km. The research was facilitated by using various software applications, including Microsoft Excel, SPSS, Matlab, GMT, and Z-map. Descriptive statistics were employed to analyze the hypocenter and epicenter of the earthquake distribution. In contrast, the maximum likelihood method was employed to ascertain the seismicity value and earthquake return period. The findings indicate that the earthquake distribution is relatively dense, except in certain regions within the sea area. The results of the seismicity analysis demonstrate that Sub-region I exhibits the highest level of seismic activity. At the same time, the shortest return period is observed at a magnitude of 3.0 Mw, specifically within Sub-region I.